Hypergeometric Hodge modules - Reichelt, Thomas; Sevenheck, Christian (Algebraic geometry, 2020)
We consider mixed Hodge module structures on GKZ hypergeometric diﬀerential systems. We show that the Hodge ﬁltration on these D-modules is given by the order ﬁltration, up to a suitable shift. As an application, we prove a conjecture on the existence of non-commutative Hodge structures on the reduced quantum D-module of a nef complete intersection inside a toric variety.